Protective effect of advanced age on post‐ERCP pancreatitis and unplanned hospitalisation. Issue 10 (October 2015) - Maitin‐Casalis, N.; Neeman, T.; Thomson, A.
Abstract Background As the median age of Australia's population rises, endoscopic retrograde cholangiopancreatography (ERCP) is becoming increasingly used in the elderly. However, ERCP remains associated with serious complications including post‐ERCP pancreatitis (PEP), which often necessitate unplanned hospital admission. Although previous research has demonstrated a protective effect of age against PEP, inconsistencies have arisen in recent studies. In addition to age, post‐ERCP complication rates have been previously shown to be affected by various factors including longer procedure duration and high‐risk indications. Aim The aim of this study was to investigate the rates of PEP and unplanned hospital admission or prolongation of hospital stay (UHAP) across age groups and their relation to procedure duration and indication. Methods Prospective analysis of 1284 consecutive ERCP on patients aged 20–101 years performed at a tertiary referral centre. Results Advanced age (>80 years) was associated with a significantly lower risk of both PEP (P = 0.02) and UHAP (P < 0.05) compared with patients aged 50–79 years. Rates of PEP and UHAP differed significantly according to indication (P < 0.01) and longer procedure duration similarly increased the risk of both complications (P < 0.01). However, there were no significant differences between age groups in terms of the proportion of patients with 'high‐risk' indications. Importantly, age remained a significant negative predictor of PEP even after adjusting for procedure duration (P = 0.04). Conclusions The protective effect of age against PEP and UHAP is not due to confounding by high‐risk indications or increased procedure duration. ERCP may be a relatively safe option for our growing cohort of elderly patients.